The Comparison of MTT and CVS Assays for the Assessment of Anticancer Agent Interactions - Śliwka, Lidia; Wiktorska, Katarzyna; Suchocki, Piotr; Milczarek, Małgorzata; Mielczarek, Szymon; Lubelska, Katarzyna; Cierpiał, Tomasz; Łyżwa, Piotr; Kiełbasiński, Piotr; Jaromin, Anna; Flis, Anna; Chilmonczyk, Zdzisław (PLOS ONE, 2016)
Multiple in vitro tests are widely applied to assess the anticancer activity of new compounds, including their combinations and interactions with other drugs. The MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay is one of the most commonly used assays to assess the efficacy and interactions of anticancer agents. However, it can be significantly influenced by compounds that modify cell metabolism and reaction conditions. Therefore, several assays are sometimes used to screen for potential anticancer drugs. However, the majority of drug interactions are evaluated only with this single method. The aim of our studies was to verify whether the choice of an assay has an impact on determining the type of interaction and to identify the source of discrepancies. We compared the accuracy of MTT and CVS (crystal violet staining) assays in the interaction of two compounds characterized by similar anticancer activity: isothiocyanates (ITCs) and Selol. Confocal microscopy studies were carried out to assess the influence of these compounds on the reactive oxygen species (ROS) level, mitochondrial membrane potential, dead-to-live cell ratio and MTT-tetrazolium salt reduction rate. The MTT assay was less reliable than CVS. The MTT test of Selol and 2-oxoheptyl ITC, which affected the ROS level and MTT reduction rate, gave false negative (2-oxoheptyl ITC) or false positive (Selol) results. As a consequence, the MTT assay identified an antagonistic interaction between Selol and ITC, while the metabolism-independent CVS test identified an additive or synergistic interaction. In this paper, we show for the first time that the test assay may change the interpretation of the compound interaction. Therefore, the test method should be chosen with caution, considering the mechanism of action of the compound.